THE ROLE OF FAULTING ON THE GROWTH OF MIOCENE CARBONATE PLATFORMS IN CENTRAL LUCONIA PROVINCE, SARAWAK - JAMALUDIN, SITINUR FATHIYAH (2014)
Tectonics in addition to the other environmental factors impacts the growth of carbonate platforms and plays an important role in shaping the internal architecture of the platforms. Detailed of faults' development and healing in carbonate environment have not been explored sufficiently especially in the South East Asia region.